2007
DOI: 10.1681/asn.2006070806
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase p22phox and Catalase Gene Variants Are Associated with Biomarkers of Oxidative Stress and Adverse Outcomes in Acute Renal Failure

Abstract: Reactive oxygen species are important mediators of injury in acute renal failure (ARF). Although polymorphisms that affect key pro-and antioxidant enzymes might alter the susceptibility to oxidative stress-mediated injury, the use of genetic epidemiology for the study of oxidative stress-related genes has received little attention in ARF. The relationship of single-nucleotide polymorphisms in the coding region (C to T substitution at position ؉242) of the pro-oxidant enzyme NADPH oxidase p22phox subunit gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 40 publications
4
67
1
2
Order By: Relevance
“…A study conducted by Perianayagam et al on 200 AKI patients found that C4T polymorphism at position 262 of the CAT gene was not associated with AKI. 29 However, in our study, the genotype distributions of the rs769217 polymorphism of the CAT gene were similar in the AKI and the control groups. It was determined that carrying a T allele in the ninth exon position of the CAT gene was associated with a six-fold increase in intensive care requirements and a ten-fold increase in hospital mortality.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…A study conducted by Perianayagam et al on 200 AKI patients found that C4T polymorphism at position 262 of the CAT gene was not associated with AKI. 29 However, in our study, the genotype distributions of the rs769217 polymorphism of the CAT gene were similar in the AKI and the control groups. It was determined that carrying a T allele in the ninth exon position of the CAT gene was associated with a six-fold increase in intensive care requirements and a ten-fold increase in hospital mortality.…”
Section: Discussioncontrasting
confidence: 48%
“…28 It has been reported that in AKI patients, the NADPH oxidase p22phox gene polymorphism was associated with dialysis requirements and death. 29 In our study, it was similarly determined that gene polymorphism of CAT, an antioxidant enzyme, was also related to intensive care requirements and in-hospital mortality. In addition, a study related to MnSOD gene polymorphisms showed that the gene polymorphisms in this enzyme were related to kidney functions.…”
Section: Discussionmentioning
confidence: 69%
“…In a study of 200 patients with mixed-cause AKI, Perianayagam et al (33) examined the association of polymorphisms in NADPH Oxidase p22phox and Catalase, two enzymes involved with the regulation of reactive oxygen species, with dialysis and mortality. Individuals with the T allele in the NADPH Oxidase p22phox gene possessed a greater risk of dialysis or mortality (unadjusted OR ϭ 2.11).…”
Section: Oxidative Stress Genesmentioning
confidence: 99%
“…No association was demonstrated between the Catalase gene and AKI. This study was unique in that it is one of two studies that examined associations with firm outcomes, i.e., dialysis or mortality (16,33).…”
Section: Oxidative Stress Genesmentioning
confidence: 99%
“…In ARF, NAD(P)H oxidase and catalase gene variants are associated with biomarkers of oxidative stress and adverse outcomes. 23 Additionally, Nishiyama et al have reported that aldosterone-induced renal injury is associated with increases in expression of NAD(P)H oxidase components and ROS levels. 24 Furthermore, in angiotensin II induced oxidative stress, renal damage has been reported to be via the activation of NAD(P)H oxidase.…”
Section: Absorbancementioning
confidence: 99%